Impacts of drinking-age laws on mortality in Canada, 1980-2009 - Callaghan, R.; Sanches, M.; Gatley, J.; Stockwell, Tim (Elsevier Ireland Ltd, 2014)
Background: Given the recent international debates about the effectiveness and appropriate age setpoints for legislated minimum legal drinking ages (MLDAs), the current study estimates the impact of Canadian MLDAs on mortality among young adults. Currently, the MLDA is 18 years in Alberta, Manitoba and Québec, and 19 years in the rest of Canada. Methods: Using a regression-discontinuity approach, we estimated the impacts of the MLDAs on mortality from 1980 to 2009 among 16- to 22-year-olds in Canada. Results: In provinces with an MLDA of 18 years, young men slightly older than the MLDA had significant and abrupt increases in all-cause mortality (14.2%, p = 0.002), primarily due to deaths from a broad class of injuries [excluding motor vehicle accidents (MVAs)] (16.2%, p = 0.008), as well as fatalities due to MVAs (12.7%, p = 0.038). In provinces/territories with an MLDA of 19 years, significant jumps appeared immediately after the MLDA among males in all-cause mortality (7.2%, p = 0.003), including injuries from external causes (10.4%, p < 0.001) and MVAs (15.3%, p < 0.001). Among females, there were some increases in mortality following the MLDA, but these jumps were statistically non-significant. Conclusions: Canadian drinking-age legislation has a powerful impact on youth mortality. Given that removal of MLDA restrictions was associated with sharp upturns in fatalities among young men, the MLDA likely reduces population-level mortality among male youth under the constraints of drinking-age legislation. Alcohol-control policies should target the transition across the MLDA as a pronounced period of mortality risk, especially among males.